A country specific point of view on international diversification. (November 2019) - Kellner, Ralf; Rösch, Daniel
Highlights: This paper analyzes diversification potential of financial markets beyond continental level. Not necessarily the development status of an economy determines its potential in diversification. Diversification seems to be strongly related to geographical distance. Low marignal risk contribution and multivariate tail dependence determines potential in diversification. Abstract: This paper adds a country specific point of view on diversification among financial markets. Previous results indicate that emerging markets may generally exhibit higher diversification effects in comparison to developed markets due to lower market linkages. However, the question remains which markets in particular may be more or less attractive among emerging and developed markets as well as in a world market setting. To the best of our knowledge, this is the first empirical study which analyzes this question beyond continental levels only. We analyze diversification by means of optimal portfolio allocations and in terms of tail risk reductions. We also include investors' tendency to overweight regional investments (home bias). Our results show that Malaysia, Switzerland, Jordan, Chile or Singapore are markets with high diversification potential. On the contrary, Argentina, Brazil and South Korea exhibit high individual risk levels in combination with high market linkages.